Pengaruh Glukomanan Terhadap Penurunan Risiko Penyakit Stroke Iskemik - Muhammad Amin Bayu Oktarian Alamsyah (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Stroke is the second highest cause of death in the world. Ischemic stroke is a neurological deficit that occurs when blood vessels that supply the brain are blocked. This disease occurs due to one of which is atherosclerosis in the arteries that carry blood to the brain. Atherosclerosis occurs due to plaque consisting of cholesterol carried by the bloodstream to cause blockages in the arteries. One way to reduce the risk of ischemic stroke is to go on a high-fiber diet. Foods high in fiber, especially water-soluble fiber, are known to reduce cholesterol levels in the blood circulation. A number of studies have concluded that water-soluble fiber, such as glucomannan, can reduce blood cholesterol levels. Glucomannan can reduce cholesterol levels by binding to bile salts and stimulating the formation of new bile salts. This fiber will inhibit the recycling process and bile salts will be secreted through the feces so that only a little bile salt is returned again in the liver. This will stimulate the liver to form new bile salts and will take cholesterol from the blood as a bile salt-forming material. The more bile salt is formed, the cholesterol circulating in the blood will decrease